A fuzzy-based risk assessment model for evaluations of hazards with a real-case study - Tepe, Serap; Kaya, Ihsan (TAYLOR & FRANCIS INC, 2020)
The effectiveness of the traditional risk analysis approach is enhanced by the integration of the fuzzy logic and Multi-Criteria Decision Making (MCDM) methods. In fact, human decisions are ambiguous and blurred and do not fit to express with absolute numerical values. For this reason, it is more realistic to use verbal variables in modeling human decisions. In this paper, a new fuzzy based hazard evaluation approach is proposed to deal with the risk assessment process. The proposed methodology consists on MCDM with a fuzzy system which includes a hybrid structure consists the Pythagorean Fuzzy Analytic Hierarchy Process (PFAHP) method with cosine similarity, and also Neutrosophic Analytic Hierarchy Process (NFAHP) to support facing of uncertainty in the risk assessment process for asphalt production, laying and coating services which are important and should be examined in terms of occupational health and safety. To the best of our knowledge, this study is the first to propose facing uncertainty in the hazard evaluations and risk assessment for asphalt production, laying, and coating services. As an outcome of the analysis by the proposed method, according to PFAHP and NFAHP methodologies the criterions manometer size and calibration are found to be most critical factors, respectively.
Keywords: Risk assessment; hazard evaluations; occupational health and safety; fuzzy sets; Pythagorean; neutrosophic; analytic hierarchy process; asphalt production factory; SETS; SELECTION; AHP; ALTERNATIVES; HEALTH; SAFETY; TOOL; Biodiversity & Conservation; Environmental Sciences & Ecology